Phosphorus in agricultural constructed wetland sediment is sparingly plant-available - Laakso, Johanna; Uusitalo, Risto; Heikkinen, Janne; Yli-Halla, Markku (Wiley, 2017)
Agricultural constructed wetlands (CWs) are intended to retain sediment and phosphorus (P) carried off with runoff and drainage water. The accumulated sediment, with adsorbed P, is often advised to be recycled to agricultural land, but little is known about the fertilizer value of sediment-associated P. This study examined the effects on P adsorption characteristics and P plant availability of mixing CW sediment into soil. Although the total P content in the sediment was approximately equal to that in catchment soil and the NaOH-extractable P content was higher to that in catchment soil, in adsorption-desorption tests sediment P solubility decreased and affinity for P increased with increasing addition rate of CW sediment to soil. Already the lowest sediment addition rate (12.5% of dry weight) decreased the equilibrium P concentration (EPC0') by 60% on average compared to unamended catchment soil. In a greenhouse pot experiment, Italian ryegrass (Lolium multiflorum L.) yield was largely unaffected by CW sediment application, but P uptake systematically decreased when the rate of sediment application to soil increased. When 12.5% dry weight of sediment was added, plant P uptake decreased by 6-50% in P-unfertilized pots and by 6-17% in P-fertilized pots (150 mg P kg(-1)) compared with P uptake of ryegrass grown in unamended field soil. Our other results suggest that the plant availability of P in CW sediments is very low due to high clay content and high concentrations of aluminium (Al) and iron (Fe) (hydr)oxides in the sediment. Thus, if applied to agricultural fields in large quantities, dredged CW sediment may impair crop P supply.
Keywords: fosfori; ravinteiden otto; italianraiheinä; nutrient availability; phorphorus; Lolium multiflorum